P10 Whole-exome-Sequencing-based discovery of novel syndromic form of neonatal cholestasis. (6th September 2011) - Hartley, J L; Simpson, M; Tee, L; Brown, R M; Kirkham, S; Pasha, S; Trembath, R C; Gissen, P; Maher, E R; Kelly, D A; Morgan, N V
Abstract : Introduction: Two cousins from a consanguineous family presented with low γ glutamyl transferase (GGT) cholestasis, trichorrhexis nodosa (TN) and severe hypoglycaemia which required diazoxide to stabilise. One child also had life threatening diarrhoea necessitating parenteral nutrition, which suggested the possible diagnosis of trichohepatoenteric syndrome (THES). However screening of the THES gene ( TTC37 ) excluded mutations. Aim: The aim of this study was to identify the molecular genetic defect in this family and hence further understanding of unexplained cholestasis within a multisystem disorder. Method: We used a novel combination of autozygosity mapping combined with whole-exome-sequencing (WES). An Affymetrix 250K SNP chip genome-wide linkage scan was used to identify common regions of shared homozygosity. SureSelect human All Exon kit (Agilent Technologies) and Illumina GaIIx was used for WES of both individuals. Single nucleotide substitutions and small insertion deletions were identified. Filtering of variants for novelty was performed by comparison to dbSNP131 and 1000 Genomes pilot SNP calls (March 2010) and variants identified in 40 control exomes sequenced and analysed by the same method described above. Results: The largest overlapping autozygous regions were at chromosome 7, 16, 20, 12 and 4. The whole exome sequencing identified 17 844 and 17 867 variations in patients 1 and 2 respectively. Of these only three homozygous non-synonymous variants and one frameshift variant were found in both patients in the identified homozygous regions. The frameshift was a homozygous single base G deletion (c.587delG) in exon 6 of AKR1D1 which mapped within the candidate homozygous region in chromosome 7. The variant results in a frameshift at amino acid 196 leading to a premature stop codon 11 amino acids downstream (p.Cys196SerfsX11). AKR1D1 encodes the enzyme δ 4 -3-oxosteroid 5β-reductase that is required for the synthesis of chenodeoxycholic and cholic acids important for normal bile flow. Mutations in AKR1D1 have previously been described in patients with severe neonatal liver disease. Conclusion: In conclusion we have extended the clinical features of bile salt synthesis disorders resulting from mutations in AKR1D1 to include a severe form of low GGT cholestasis, TN and severe hypoglycaemia which may be amenable to treatment with bile salt supplementation. Combining the technique of whole genome linkage mapping and WES creates a powerful tool to elucidate the molecular basis of uncharacterised genetic disorders.